Diabetes and Its Complications: Therapies Available, Anticipated and Aspired - Grover, Anu; Sharma, Komal; Gautam, Suresh; Gautam, Srishti; Gulati, Monica; Singh, Sachin K. (Current Diabetes Reviews, 2021)
Worldwide, diabetes ranks among the ten leading causes of mortality. Prevalence of diabetes is growing rapidly in low and middle income countries. It is a progressive disease leading to serious co-morbidities, which results in increased cost of treatment and over-all health system of the country. Pathophysiological alterations in Type 2 Diabetes (T2D) progressed from a simple disturbance in the functioning of the pancreas to triumvirate to ominous octet to egregious eleven to dirty dozen model. Due to complex interplay of multiple hormones in T2D, there may be multifaceted approach in its management. The ‘long-term secondary complications’ in uncontrolled diabetes may affect almost every organ of the body, and finally may lead to multi-organ dysfunction. Available therapies are inconsistent in maintaining long term glycemic control and their long term use may be associated with adverse effects. There is need for newer drugs, not only for glycemic control but also for prevention or mitigation of secondary microvascular and macrovascular complications. Increased knowledge of the pathophysiology of diabetes has contributed to the development of novel treatments. Several new agents like Glucagon Like Peptide - 1 (GLP-1) agonists, Dipeptidyl Peptidase IV (DPP-4) inhibitors, amylin analogues, Sodium-Glucose transport -2 (SGLT- 2) inhibitors and dual Peroxisome Proliferator-Activated Receptor (PPAR) agonists are available or will be available soon, thus extending the range of therapy for T2D, thereby preventing its long term complications. The article discusses the pathophysiology of diabetes along with its comorbidities, with a focus on existing and novel upcoming antidiabetic drugs which are under investigation. It also dives deep to deliberate upon the novel therapies that are in various stages of development. Adding new options with new mechanisms of action to the treatment armamentarium of diabetes may eventually help improve outcomes and reduce its economic burden.
Keywords: Type 2 Diabetes